2019
DOI: 10.1128/iai.00132-19
|View full text |Cite
|
Sign up to set email alerts
|

NF-κB RelA Is Required for Hepatoprotection during Pneumonia and Sepsis

Abstract: Pneumonia and sepsis are distinct but integrally linked public health concerns. The hepatic acute-phase response (APR), which is largely dependent on transcription factors NF-B RelA and STAT3, is a hallmark of these pathologies and other injurious conditions. Inactivation of the APR can promote liver injury, a frequently observed organ dysfunction during sepsis. However, whether or how the acute-phase changes promote liver tissue resilience during infections is unclear. To determine the hepatoprotective role o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 59 publications
0
3
0
Order By: Relevance
“…The specific role of miR-181a-5p in BMDM during K. pneu infection is still unclear and requires further investigation in the future. Moreover, STAT3 has been revealed to play important roles in K. pneu infection-related injury [ 32 , 33 ]. Here, we identified that miR-181a-5p was able to inhibit STAT3 expression at posttranscriptional levels and repressed Nlrp3 and Asc expression in BMDM.…”
Section: Discussionmentioning
confidence: 99%
“…The specific role of miR-181a-5p in BMDM during K. pneu infection is still unclear and requires further investigation in the future. Moreover, STAT3 has been revealed to play important roles in K. pneu infection-related injury [ 32 , 33 ]. Here, we identified that miR-181a-5p was able to inhibit STAT3 expression at posttranscriptional levels and repressed Nlrp3 and Asc expression in BMDM.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB signaling pathway plays a key role in the cellular inflammatory response and immune response, and the regulation of the NF-κB signaling pathway can reduce the injury to the liver, lung and kidney caused by pneumonia. 51 , 52 HIF-1 is a transcription factor and can be used as the main regulator of oxygen homeostasis, and the HIF-1 signaling pathway is related to the release of inflammatory cytokines in viral pneumonia. 53 TNF is a proinflammatory cytokine that plays an important role in cell proliferation, differentiation and apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK1 plays an important role in the pathological process of preeclampsia [46]. RELA is essential for maintaining liver homeostasis against TNF-α driven immunotoxicity [47]. Therefore, the development of potentially active compounds as a new drug for the treatment of BD and the elucidated target gene as a new mechanism of action for the treatment of BD has very important research signi cance and innovation, which will be carried out in the next work plan.…”
Section: Discussionmentioning
confidence: 99%